Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

this exercise is from Dummit and foote , page 117 , # 7.d

prove : a transitive group $G$ is primitive on $A$ iff for each $a \in A$ , the only subgroups of $G$ containing $G_a$ are $G_a$ and $G$ where , $G_a$ is the stabilizer of $a$ $G$ is subgroup of $S_n$ - symmetric group -

my attempt ,

i proved one side , i proved that if the only subgroups of $G$ containing $G_a$ are $G_a$ and $G$ then , the transitive Group $G$ is primitive

but i couldn't prove the other side the other side .

what i had thought in that if i can prove that , if $H$ is subgroup of $G$ that contains Ga then H = GB for some subset $B$ of $A$ , $a$ is in $B$ where $GB$ = { $g \in G$ : $g$ . $B = B$, . is group action operation }

then , I can prove the statement

but I don't know excatly how to do this ! I don't know if this is true to prove it !!

i hope that you give me some hints which able me to create my own solution

thanx !

share|improve this question
add comment

1 Answer

up vote 4 down vote accepted

Suppose $G$ is primitive on $A$. Hence the only blocks of $A$ are the singleton sets and $A$ itself. Take $a\in A$ and suppose $H\leq G$ is a subgroup such that $G_a\leq H\leq G$. Consider $Ha=\{ha:h\in H\}$.

  • Prove that $Ha$ is a block.

Let $\sigma\in G$ as in the text. Suppose there exists some $x\in Ha\cap\sigma(Ha)$. So there are $h_1,h_2\in H$ such that $h_1a=\sigma h_2a$. This implies $h_1^{-1}\sigma h_2a=a$, hence $h_1^{-1}\sigma h_2\in G_a$. But $G_a\leq H$, and thus $\sigma\in H$ by left and right multiplying by $h_1$ and $h_2^{-1}$. But then $\sigma(Ha)=Ha$ since $Ha$ is invariant under the action of $H$, so $Ha$ is a block.

After proving that, we know there are two cases by primitivity, so either $Ha=A$, or $Ha=\{a\}$.

If $Ha=A$, for every $g\in G$ we can find $h\in H$ such that $ga=ha$, since the action is transitive. But then $h^{-1}ga=a$, thus $h^{-1}g\in G_a\leq H$, whence $g\in H$. It follows immediately that $H=G$ in fact.

The other case is simpler.

If $Ha=\{a\}$, then for every $h\in H$, $ha=a$, thus $H\leq G_a$, so $H=G_a$.

So if $a\in A$, and $H\leq G$ with $G_a\leq H\leq G$, we have either $H=G_a$ or $H=G$. So $G_a$ is maximal in $G$, as we needed to show.

share|improve this answer
    
why did you delete the first paragraph of your answer ?!! –  Maths Lover Jan 25 '13 at 23:55
    
@MathsLover It was needed to prove the converse direction, but I saw that you had already proven that. I removed it since it didn't seem relevant. –  Ben West Jan 26 '13 at 0:22
    
if i want to prove the paragraph which you had deleted . if A=B then GB = { g in G : g.B=B } = { g in G : g.A=A } = GA = G the other side as follows , if GB = G then G = { g in G : g . A = A } = { g in GB : g . A = A } this implies that A ⊆ B , but B ⊆ A then A=B is this proof is true for the paragraph deleted ? –  Maths Lover Jan 26 '13 at 0:29
    
the comment above is for you . –  Maths Lover Jan 26 '13 at 0:36
    
why x∈(x y)(B) ?? , x∈B , (x y)(x) = y ! so x is not in (x y)(B) . –  Maths Lover Jan 26 '13 at 0:45
show 11 more comments

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.